Sosialisasi Pemasaran Kreatif di Era Tiktok pada Pelaku UMKM Desa Kedung Waringin - Purwatiningsih Purwatiningsih; Dhuha Safria; Frida Aprillia; Alan Budi Kusuma (Jurnal Pengabdian Masyarakat Waradin, 2024)
This community service program is designed to help MSMEs in Kedung Waringin Village utilize TikTok as a creative marketing medium. A total of 22 business actors participated in the training which included theory and practice, including understanding the TikTok algorithm, creating video content, and using features such as hashtags and TikTok Shop. The results of the training showed a significant increase. Before the training, 60% of participants did not understand digital marketing, but this figure increased to 85% after the training. In addition, 90% of participants felt that the training was relevant to their business needs, and 60% of them recorded an increase in sales of up to 30% after implementing the strategies taught. This activity provides direct benefits by improving participants' skills in digital marketing and building their confidence to use technology independently. This program shows the success of a practice-based approach and can be a model for MSME empowerment that can be applied in other areas